Determination of radon gas concentrations inside different types of residential buildings in Baghdad (Journal of the College of Basic Education, 2022)
The gas radon is one of the main sources of natural radiatio which has three types of isotope s is R-222 and Rn-220 and Rn – 219 , and isotope is the first among the most important isotopes of the fact that arelatively long half – life (3.82 day). The igneous roks of the most important sources of radon in nature in addition to soil erosion resulting from these rocks and construction materials such as cement and rocks which are the basic components. The water used for drinking or for cleanliness or ground water.Used in this research cumulative indirect way to measure the concentration of radon , which relies on the use of reagents impact of nuclear- based soild –state whe the advantage of these reagents as you record and store the effects of charged particles and along period of time . Were distributed impact nuclear organic reagent (CR-39)in the middle of several places of the residen tial house in the (bed room )theliving room , the kitchen, thebathroom) and after aperiod of time atemrt every two months during the summer and winter collected from new and conducted achemical process skimming. Results presented table(1)Displayed concent ration of radon , Behigh in winter month comparison with summer month .As well as for table(2)displayed concentration of rad ,Behigh in th type of Bilding. however,this focus in within the permissible limits which is estimated (200 Bq-m-3) according to the recommendationsof the in terndtional commission on Radiological protection(ICRP).